Gallstones. Issue 12 (December 2017) - Beckingham, Ian J.
Abstract: Gallstones are the commonest surgical emergency and are responsible for over 60, 000 operations per year in the UK and 0.5 million procedures in the USA. This article explores the pathogenesis of gallstones, the presentation and management options; the technique of cholecystectomy and the prevention and recognition of bile duct injury.